1.2 Å resolution crystal structure of Escherichia coli WrbA holoprotein. (25th September 2013) - Kishko, Iryna; Carey, Jannette; Reha, David; Brynda, Jiri; Winkler, Renee; Harish, Balasubramanian; Guerra, Richard; Ettrichova, Olga; Kukacka, Zdenek; Sheryemyetyeva, Olena; Novak, Petr; Kuty, Michal; et al.
<x xml:space="preserve">Abstract</x> The Escherichia coli protein WrbA, an FMN‐dependent NAD(P)H:quinone oxidoreductase, was crystallized under new conditions in the presence of FAD or the native cofactor FMN. Slow‐growing deep yellow crystals formed with FAD display the tetragonal bipyramidal shape typical for WrbA and diffract to 1.2 Å resolution, the highest yet reported. Faster‐growing deep yellow crystals formed with FMN display an atypical shape, but diffract to only ∼1.6 Å resolution and are not analysed further here. The 1.2 Å resolution structure detailed here revealed only FMN in the active site and no electron density that can accommodate the missing parts of FAD. The very high resolution supports the modelling of the FMN isoalloxazine with a small but distinct propeller twist, apparently the first experimental observation of this predicted conformation, which appears to be enforced by the protein through a network of hydrogen bonds. Comparison of the electron density of the twisted isoalloxazine ring with the results of QM/MM simulations is compatible with the oxidized redox state. The very high resolution also supports the unique refinement of Met10 as the sulfoxide, confirmed by mass spectrometry. Bond lengths, intramolecular distances, and the pattern of hydrogen‐bond donors and acceptors suggest the cofactor may interact with Met10. Slow incorporation of FMN, which is present as a trace contaminant in stocks of FAD, into growing crystals may be responsible for the near‐atomic resolution, but a direct effect of the conformation of FMN and/or Met10 sulfoxide cannot be ruled out.